2019
DOI: 10.1111/are.14022
|View full text |Cite
|
Sign up to set email alerts
|

The growth and apparent digestibility of white shrimp,Litopenaeus vannamei, are increased with the probiotic,Bacillus subtilis

Abstract: The aims of this study were to evaluate the probiotic efficiency of Bacillus subtilis E20 (109 colony‐forming units kg−1) on the growth and apparent digestibility coefficients (ADCs) of dry matter (DM), crude protein (CP), amino acids (AAs), and crude lipids (CLs) of the white shrimp, Litopenaeus vannamei. A control diet without probiotic supplementation was used. Shrimp exhibited significant increases in growth performance and feed utilization after being fed the test diet for 56 days. Shrimp were then used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…It has been shown that use of Bacillus to the rearing water can make a balance between the micro-organisms in the water column or in the pond soil through a bacterial competition with a consequence in the decreasing in load of secondary bacterial pathogens (Kumar et al 2016). Bacillus also provide a suitable condition in the GI tracts of fish and shellfish, by improving digestion and absorption of the nutrients, which in turn improve the animal growth performance (Ghosh et al 2019;Meidong et al 2018;Li et al 2019;Soltani et al 2019b;Mukherjee et al 2019b;Zhou et al 2019;Vogeley et al 2019;Tsai et al 2019). However, further studies on mode of actions are needed.…”
Section: Bacillus As Probiotics For Finfish and Shellfishmentioning
confidence: 99%
“…It has been shown that use of Bacillus to the rearing water can make a balance between the micro-organisms in the water column or in the pond soil through a bacterial competition with a consequence in the decreasing in load of secondary bacterial pathogens (Kumar et al 2016). Bacillus also provide a suitable condition in the GI tracts of fish and shellfish, by improving digestion and absorption of the nutrients, which in turn improve the animal growth performance (Ghosh et al 2019;Meidong et al 2018;Li et al 2019;Soltani et al 2019b;Mukherjee et al 2019b;Zhou et al 2019;Vogeley et al 2019;Tsai et al 2019). However, further studies on mode of actions are needed.…”
Section: Bacillus As Probiotics For Finfish and Shellfishmentioning
confidence: 99%
“…To date, approximately 20 genera of bacteria have been shown to have a probiotic effect in shrimp, although the majority of research has focused on Bacillus and lactic acid bacteria (LAB), such as Lactobacillus (Tables 1–3), due largely to their prevalence and successful application as probiotics in mammals and poultry. Probiotics can be administered orally with the feed (including bioencapsulation with live food vectors such as artemia; Immanuel, 2016), directly into the water as purified cultures or spores (Ringø, 2020), or within a fermented growth media, for example Bacillus subtilis E20‐fermented soybean meal (Liu et al ., 2009, 2010; Tseng et al ., 2009; Tsai et al ., 2019; Wang et al ., 2019). Similarly, probiotics may be administered in combination with a complementary prebiotic, ‘a non‐digestible food ingredient that beneficially affects the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the colon’ (Gibson & Roberfroid, 1995), to form treatments known as ‘symbiotics’ (Schrezenmeir & de Vrese, 2001; Li et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, in earlier studies, Adel et al (2017) and Won et al (2020) reported that dietary supplementation of P. pentosaceus could cause a significant improvement in the growth performance and nutritional utilization in L. vannamei, findings in agreement with that of our study. There are also studies on whiteleg shrimp in which improved growth and feed utilization in response to feeding diets supplemented with probiotics, such as Bacillus subtilis (Munaeni et al, 2014;Tsai et al, 2019;Won et al, 2020), Bacillus licheniformis (Fan et al, 2021), and Lactococcus lactis (Won et al, 2020), were reported. In another study, the use of 0.2-0.4% FOS in shrimp diets was shown to improve the growth performance, FCR, and the microbial diversity, and to suppress several potential pathogens, such as Vibrio tubiashii, V. parahaemolyticus, and Photobacterium damselae-like strains in the intestine of whiteleg shrimp (Hu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the important role of probiotics in the competitive exclusion of pathogenic bacteria, nutrient, and enzymatic contribution to shrimp digestion, enhancement of the shrimp immune response, and antiviral effects (Hoseinifar et al, 2018;Ringø, 2020). Probiotics can be administered orally with the feed, or directly into the shrimp rearing water as purified cultures or spores (Ringø, 2020), or in a fermented growth media, for example, Bacillus subtilis E20-fermented soybean meal (Tsai et al, 2019;Wang et al, 2019). Similarly, probiotics may be administered in combination with a nondigestible food ingredient (i.e., prebiotics) that beneficially affects the host by causing synergistic effects, an approach referred to as "synbiotics" (Schrezenmeir and de Vrese, 2001;Li et al, 2018;Knipe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%